DIGITAL MARKETING STRATEGY FOR CLOTHING BRAND “KOMO” (The Indonesian Journal of Business Administration, 2019)
At this time the creative economy in Indonesia will become an economic sector that is no less important than agriculture, industry and information. Especially in the creative fashion industry that is developing in Indonesia, which is supported by the rapid development of internet technology. So that the market place and online platforms that change shopping habits to shop online. KOMO is one of the fashion brands, needs a plan for effective digital marketing so that it is not left behind by other competitors. The main objective of this research is to find out the source of the problems that occur in KOMO so that they can formulate the best digital marketing strategy and can increase sales. This study uses internal and external analysis, for internal analysis using the STP analysis method and marketing mix while external analysis uses market analysis methods, competitor analysis, and customer analysis. From the results of this analysis it can be seen through fishbone diagrams there are 4 factors that affect KOMO's sales level, namely place, product, promotion, and human resource. From these results, the researcher formulated a solution to implemented by KOMO in the form of a digital marketing strategy.Keywords: KOMO, Digital marketing, Creative Economy, Fashion Industry, Market Place, Online Platform